Combined EUS LAMS and Percutaneous Fully Covered SEMS-Guided Direct Endoscopic Necrosectomy (e-DEN + p-DEN) for Walled-Off Pancreatic Necrosis with Paracolic Extension - Gandhi, Ashish; Borkar, Mangesh; Bapaye, Harsh; Pujari, Rajendra; Bapaye, Amol (Journal of Digestive Endoscopy, 2021)
Management of infected lesser sac walled-off pancreatic necrosis (WOPN) is technically challenging and involves endoscopic ultrasound (EUS)-guided transmural drainage using either lumen-apposing metal stent (LAMS) or multiple plastic stents as the standard approach. A step-up approach—drainage followed by additional direct endoscopic necrosectomy (DEN) whenever required—has been a standard recommendation. Collections extending to the paracolic gutter are difficult to manage endoscopically and often require additional surgical intervention. In this video case, we describe a combined approach using EUS-guided LAMS and percutaneous fully covered self-expandable metal stent-guided DEN (e-DEN + p-DEN) for successful management of an infected lesser sac WOPN with paracolic extension.
Keywords: walled-off pancreatic necrosis; WON; WOPN; percutaneous direct endoscopic necrosectomy; direct endoscopic necrosectomy; DEN; DEN; p-DEN